Evidence for a shared cognitive mechanism underlying relative rhythmic and melodic perception - Jeroen van der Aa; W. Tecumseh Fitch (Frontiers in Psychology)
Musical melodies and rhythms are typically perceived in a relative manner: two melodies are considered “the same” even if one is shifted up or down in frequency, as long as the relationships among the notes are preserved. Similar principles apply to rhythms, which can be slowed down or sped up proportionally in time and still be considered the same pattern. We investigated whether humans perceiving rhythms and melodies may rely upon the same or similar mechanisms to achieve this relative perception. We looked at the effects of changing relative information on both rhythm and melody perception using a same-different paradigm. Our manipulations changed stimulus contour and/or added a referent in the form of either a metrical pulse (bass-drum beat) for rhythm stimuli, or a melodic drone for melody stimuli. We found that these manipulations had similar effects on performance across rhythmic and melodic stimuli. To our knowledge, this is the first study showing that the addition of a drone note has significant effects on melody perception, warranting further investigation. Overall, our results are consistent with the hypothesis that relative perception of rhythm and melody rely upon shared relative perception mechanisms, alongside domain specific mechanisms. Further work is needed to explore the specific nature of this relationship and to pinpoint the cognitive and neural mechanisms involved.